2009
DOI: 10.1095/biolreprod.108.073130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leptin on Mouse Trophoblast Giant Cells1

Abstract: Leptin plays a role in both energy homeostasis and reproduction, and it is required in early pregnancy. It stimulates metalloproteinase activity in cultured human trophoblasts and invasiveness of cultured mouse trophoblasts. Our goal has been to examine mechanisms that underpin the ability of leptin to promote trophoblast invasiveness in primary cultures of mouse trophoblasts. Leptin stimulated the phosphorylation of MEK (MAP2K1) but not signal transducer and activator of transcription 3 (STAT3) in the culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
2
12
0
1
Order By: Relevance
“…This was not due to a sampling error caused by controlling our cohort to exclude extremes of litter size and genotype ratio, as when we pooled the data for all crosses generated, Null females consistently produced approximately one additional conceptus compared with WT or Mat females (WT and Mat mean litter size = 7.0 ± 0.3, n = 40 litters; Null mean litter size 8.2 ± 0.3, n = 48 litters, p < 0.001, Mann Whitney test). Appropriate maternal leptin levels are necessary for conception and survival of the early embryo[16]; leptin increases the invasiveness of the early embryo[17] and enhances ovulation[18]. Our finding that Null females had increased fecundity is consistent with their elevated leptin levels (Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
“…This was not due to a sampling error caused by controlling our cohort to exclude extremes of litter size and genotype ratio, as when we pooled the data for all crosses generated, Null females consistently produced approximately one additional conceptus compared with WT or Mat females (WT and Mat mean litter size = 7.0 ± 0.3, n = 40 litters; Null mean litter size 8.2 ± 0.3, n = 48 litters, p < 0.001, Mann Whitney test). Appropriate maternal leptin levels are necessary for conception and survival of the early embryo[16]; leptin increases the invasiveness of the early embryo[17] and enhances ovulation[18]. Our finding that Null females had increased fecundity is consistent with their elevated leptin levels (Supplementary Fig.…”
Section: Resultssupporting
confidence: 72%
“…Adult health has been shown to be particularly vulnerable to programming by food restriction during early pregnancy. Because leptin influences such variables as embryo implantation [12], placental cell differentiation [50] and placental amino acid transport [51], as well as fetal muscle and skeletal development [13,14] the shortage of leptin following food restriction that we have demonstrated here is worthy of future study as one route by which by which food restriction exerts its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a recent study by Schulz et al (2009) suggested that leptin influences TGC differentiation. Leptin accelerates disappearance of non-giant cells while inhibiting terminal differentiation of committed giant cells, possibly by maintaining cells in an intermediate stage of differentiation.…”
Section: Molecular Pathways Regulating Tgc Differentiationmentioning
confidence: 98%